Directed evolution of activation-induced cytidine deaminase (AID) in its natural environment - Espadinha, Daniel António Burgos (2010)
Tese de mestrado, Biologia (Biologia Humana e Ambiente), 2009, Universidade de Lisboa, Faculdade de Ciências